A mixed‐methods characterisation of patient safety incidents by primary eye care practitioners. (31st July 2022) - MacFarlane, Elinor; Carson‐Stevens, Andrew; North, Rachel; Ryan, Barbara; Acton, Jennifer
Abstract: Purpose: Patient safety in eye health care is an underdeveloped field of research. A patient safety incident occurs when an unintended incident happens that could have (or did) lead to harm. To enable learning from patient safety incidents in optometry, a characterisation of commonly experienced safety incidents is needed to identify options to improve the quality of care. This study aimed to characterise eye health‐related patient safety incidents from the perspective of eye care practitioners. Methods: At a national conference in Wales, 56 eye care practitioners participated in a stakeholder workshop on eye care‐related patient safety incidents. Participants were asked to suggest patient safety incidents that have occurred, or based on their experience, could occur in optometric practice. Using the nominal group technique, participants voted on the incident they perceived could cause the most harm and the incident observed most frequently in practice. Framework analysis supported identification of themes about the nature and outcomes of incidents in eye care. Results: Diagnostic incidents were perceived to be the most severe (highest number of 'severity votes', n  = 38), whilst administration‐related incidents were most frequent (highest number of 'frequency votes' n  = 39). Four themes were identified which are as follows: inappropriate clinical decision‐making; delayed or missed referral of patients to general medical practitioners or ophthalmologists; compromised communication with other practitioners or patients and delays in receiving eye care. The results suggest that incidents relating to inappropriate clinical decision‐making could result in the most severe harm to patients but may not occur frequently. Conclusions: Diagnostic‐ and administrative‐related incidents pose clear challenges for improvement in quality and safety of care. The breadth of themes reflecting the nature and outcomes from unsafe eye care highlights the complexity underpinning incidents and the burden to patients. This work has informed the content of an all‐Wales incident report form for primary eye care practitioners.